1990
DOI: 10.1002/jor.1100080203
|View full text |Cite
|
Sign up to set email alerts
|

Excursion of the flexor digitorum profundus tendon: A kinematic study of the human and canine digits

Abstract: The most common problem following primary flexor tendon repair is the failure of the tendon apparatus to glide, secondary to the formation of adhesions. Early motion following tendon repair has been shown to be effective in reducing adhesions between the tendon and the surrounding sheath. Therefore, it is important to determine the amount of flexor tendon excursion along the digit during joint motion. In this study, the excursion between the flexor digitorum profundus (FDP) tendon and the sheath was examined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…McGrouther and Ahmed 7 reported a mean long finger tendon excursion of 17.6 mm during active movement simulated by full extension to 90°PIP joint flexion and 60°DIP joint flexion. Horibe et al 8 reported larger tendon excursions, but these were mean tendon excursions with no distinction between index and long finger FDP tendon excursions. In that study, mean tendon excursion was 30.4 mm during active movement (full extension to 105°MCP joint flexion plus 32°PIP joint flexion plus 15°DIP joint flexion).…”
Section: Discussionmentioning
confidence: 97%
“…McGrouther and Ahmed 7 reported a mean long finger tendon excursion of 17.6 mm during active movement simulated by full extension to 90°PIP joint flexion and 60°DIP joint flexion. Horibe et al 8 reported larger tendon excursions, but these were mean tendon excursions with no distinction between index and long finger FDP tendon excursions. In that study, mean tendon excursion was 30.4 mm during active movement (full extension to 105°MCP joint flexion plus 32°PIP joint flexion plus 15°DIP joint flexion).…”
Section: Discussionmentioning
confidence: 97%
“…It has been observed that DIP joint motion produces excursion of the FDP tendon of 1-2 mm per 10° of joint flexion, whereas each 10° of PIP joint flexion results in excursion of both the FDS and FDP tendons of about 1.5 mm [9,19]. A study by Silfverskiöld et al [20] almost 20 years ago using intratendinous metal markers and postoperative x-ray found a substantial decrease in the movement of tendon repairs compared with normal movement.…”
Section: High-frequency Ultrasound Assessment Of Deep Flexor Tendonmentioning
confidence: 97%
“…The use of ultrasound imaging in the postoperative course is mainly constrained by the fact that, to our knowledge, there are no data on the sonographic appearance of a sutured tendon in the various phases of the healing process. Furthermore, there is little information available in the literature on the real amount of motion at the suture site [9].…”
Section: High-frequency Ultrasound Assessment Of Deep Flexor Tendonmentioning
confidence: 99%
“…6669 The canine model for Zone II FDP tendon laceration and repair has been extensively used since 1962. 1,70 Canine flexor tendons are similar to human flexor tendons in both anatomy and function, 61,71 as well as in response to tendon injury, repair, and rehabilitation. 3,24 The canine FDP tendon size is approximately one half the size of a human FDP tendon.…”
Section: Animal Modelsmentioning
confidence: 99%